Sleep quality, depression and lipid profile among shift healthcare workers in Cairo university hospitals - Nourhan Amir Mohamed Fahmy Alshamaa; Rehab Shehata Abdel Hady (2022)
(3GdebOeI(B: (3jYJHQ GdYed HfXGe GdhQOjGJ VQhQjG ai GdeSJTajGJ dJbOje NOeI eSJeQg eeJGRI(B. (3Ydi GdQZe ef Gf GdYed HfXGe GdhQOjGJ jajO GdeLJeY GdG Gfg jDOi Gdi GVXQGH GjbGY GdSGYI GdHjhdhLjI GdJi JDOi Gdi eTGcd UMjI eKd GdGcJFGH hShA fhYjI Gdfhe hGVWQGH eSJhi Oghf GdOe(B. (3GdgOa ef GdOQGSI(B: (3OQGSI GdYdGbI Hjf GdYed HfXGe GdhQOjGJ hGdGcJFGH hfhYjI Gdfhe h GVWQGH eSJhi Oghf GdOe Hjf GdYGedjf HfXGe GdefGhHGJ ai GdQYGjI GdUMjI(B. (3WQb GdHMK(B: (3gPg OQGSI ebWYjI ejOGfjI GLQjJ Hjf YGedjf GdQYGjI GdUMjI GdefGhHjf ai eSJTajGJ LGeYI GdbGgQI ai GdaJQI ef HOGjI TgQ aHQGjQ (B2022 (3Gdi GfJgGA TgQ SHJeHQ (B2022 (3h JVefJ GdOQGSI (B90 (3YGedG HGdQYGjI GdUMjI ef Hjfge (B36 (3YGekdG HGdefGhHI GdfgGQjI GdKGHJI h (B24 (3YGedG HGdefGhHI GddjdjI GdKGHJI h (B30 (3YGedG HGdefGhHI GdeJZjQI hbO GLQi aMU GdYGedjf HGSJNOGe GSJHjGf LhOI Gdfhe hebjGS JUfja gGedJhf ddGcJFGH hJe bjGS eSJhi GdOghf GdKdGKjI h GdHQhJjfGJ GdOgfjI bdjdI GdcKGaI h YGdjI GdcKGaI HGdGVGaI Gdi fSHI GdchdjSJQhd(B.. (3GdfJGFL(B: (3ChVMJ GdOQGSI GdMGdjI hLhO GQJaGmY Ph OdGdmI EMUGFjmI Hjf YGedjf GdefGhHI GdeJZjQI hYGedjf GdefGhHI GdfgGQjI ajeG jJYdb HSGYGJ GdYed h eSJhi GdOghf HGdOe hGdfJjLI GdELeGdjI dLhOI Gdfhe hOQLI GdGcJFGH Gdcdj dgGedJhf(B. (3ceG jhLO GQJaGY Ph OdGdI GMUGFjI Hjf YGedjf GdefGhHI GddjdI GdKGHJI hYGedjf GdefGhHI GdfgGQjI ajeG jJYdb HfSHg GdchdjSJQhd hUYhHI HOA Gdfhe hGdQVG Yf Gdfhe(B. (3bO GhVMJ GdOQGSI Gf cdeG RGOJ aJQGJ GdYed HGdefGhHI GdeJZjQI cdeG RGOJ OQLGJ GdGcJFGH h GQJaGY fSHI Oghf GdOe(B. (3GdGSJfJGLGJ(B: (3GhVMJ GdOQGSI GdMGdjI Gf GdYed HfXGe GdhQOjGJ dg JGKjQ SdHi Ydi fhYjI Gdfhe h GdMGdI GdeRGLjI h eSJhi GdOghf HGdOe ceG cTaJ Yf GQJaGY eSJhi GdOghf HGdOe h eYOd GdGcJFGH h ShA LhOI Gdfhe Hjf YGedjf GdefGhHI GdeJZjQI hYGedjf GdefGhHI GddjdI GdKGHJI ebGQfI HYGedjf GdefGhHI GdfgGQjI(B. (3GdJhUjGJ(B: (3gPg GdOQGSI oJhUj HCLQGA aMhUGJ faSjI h bjGS eSJhi Oghf GdOe ai eQMdI eG bHd GdJhXja h GbGeg Jdc GdaMhUGJ HUhQI OhQjI eSJeQI ddYGedjf HeLGd GdQYGjI GdUMjI(B. (3ceG Ef gfGc MGLg Gdi JhajQ HQGeL UMjI NGUI ddYGedjf HfXGe GdhQOjGJ h GdJi JJVef HQGeL JJONd faSi h GfXeI JZPjI h eeGQSI GdQjGVI dJNaja YHA GVXQGHGJ GdMGdI GdeRGLjI h GVXQGHGJ Gdfhe(B.s
Thesis (M.Sc.)-Cairo University,2022.
Bibliography: p.101-134.
Keywords: Occupational and Environmental Medicine; Shift work